BENTUK TO OMOU DAN TO OMOTTEIRU DAN PADANANNYA DALAM BAHASA INDONESIA - Khairina Ramadhani; Arza Aibonotika; Hana Nimashita (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2019)
Abstract: In Japanese there is an expression that serves to express thoughts or opinions, namely the expression to omou. There are many form that is derived from to omou, as to omotteiru, to omotteita and to omotta. This study discuss what are the meanings and using the expression to omou and to omotteiru and its equivalent in Indonesian. The method used in this study is the translational equivalent method, which is to harmonize the expressions to omou and to omotteiru in Indonesian equivalent. From the results of this study explain that to omou have different expression in sentences. To omou has five meanings, namely to express personal opinions, reduce assertiveness, express the possibility, express intentions, express uncertainties or doubts that can be equivalent with 'menurut saya', 'saya pikir', 'saya rasa', 'saya bermaksud'. The form to omotteiru has the meaning to express opinions, express mistakes, express desires and express intentions. The form to omotteiru can be equivalent with 'saya pikir', 'menurut saya' and 'menurut pendapat saya', 'saya bermaksud', 'bertekad’ in indonesian.Key Words: Modality, Equivalent, Translational Equivalent Method